2018
DOI: 10.1063/1.5035423
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of dendrimer molecules in solvents of varying quality

Abstract: Modified inhomogeneous statistical associating fluid theory (iSAFT) density functional theory is extended to dendrimer molecules in solvents of varying quality. The detailed structures of isolated dendrimers in implicit solvent are calculated and have a semi-quantitative agreement with simulation results available in the literature. The dendrimers form dense-core structures under all conditions, while their radius of gyration follows different scaling laws. Factors that affect the quality of the solvent are sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
3
13
0
Order By: Relevance
“…The numerical algorithm is the same as in our previous paper. 32 Note that, in the previous paper, the position variable in equations 27−45 should be in the vector form r instead of the scalar form r, which is a typo. Due to the spherical symmetry of the dendrimer structure, all segment densities are only functions of radial distance from the center core, and we are able to solve these equations in only one dimension.…”
Section: ■ Theorysupporting
confidence: 85%
See 2 more Smart Citations
“…The numerical algorithm is the same as in our previous paper. 32 Note that, in the previous paper, the position variable in equations 27−45 should be in the vector form r instead of the scalar form r, which is a typo. Due to the spherical symmetry of the dendrimer structure, all segment densities are only functions of radial distance from the center core, and we are able to solve these equations in only one dimension.…”
Section: ■ Theorysupporting
confidence: 85%
“…In our previous DFT study, we found that, if we only consider dispersion, a higher temperature always improves the solvent quality regardless of the affinity between the dendrimer and solvent. 32 Here, in Figure 5, we show how temperature affects the system when dispersion and association both exist. We use the full-sites G5 dendrimer, and it is found that the dendrimer collapses when the temperature is raised from 300K to 450K and becomes less compressed at T = 600 K. As the temperature goes to infinity, which is the athermal (AS) condition, a fully swollen structure is recovered.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter fulfills in particular the relation R D ∼ S 1/2 for the overall size of the dendrimer; see the mastering of data for different values of S in Figure b. We did not observe a collapsed state, i.e., R D ∼ N D 1/3 ∼ S 1/3 , according to eq 4c , as claimed in earlier theoretical , and experimental works. Our results are in agreement with previous findings for dendrimer melts .…”
Section: Resultssupporting
confidence: 88%
“…Modeling CO 2 as a sphere is not so sufficient as the linear shape and quadrupole moments make it challenging to describe the CO 2 bulk phase behavior by an L-J sphere. Interfacial statistical associating fluid theory (iSAFT) of Tripathi and Chapman and Jain et al has the advantage of describing molecules with different sizes and shapes, which has been used for various complex inhomogeneous fluids. It can reduce to SAFT-based EoS in the bulk and parameters in which the EoS can be applied. Using a DFT approach, the computational time is greatly reduced in comparison with the simulation, and more importantly, systems that involve trace components can be naturally studied, whereas sampling problems arise for low concentration components in molecular simulation.…”
Section: Introductionmentioning
confidence: 99%